A Framework to Collect and Reuse Engineering Knowledge in the Context of Design for Additive Manufacturing. (May 2022) - Formentini, G.; Favi, C.; Mandolini, M.; Germani, M.
Abstract: Design for AM (DfAM) requires the definition of Design Actions (DAs) to optimize AM manufacturing processes. However, AM understanding is still very blurred. Often designers are challenged by selecting the right design parameters. A method to list and collect DfAM DAs is currently missing. The paper aims at providing a framework to collect DfAM DAs according to a developed ontology to create databases (DBs). DBs were tested with two real case studies and geometric features to improve identified. Future developments aim at widening the database to provide all-around support for AM processes.